2020
DOI: 10.1038/s41539-020-0062-0
|View full text |Cite
|
Sign up to set email alerts
|

Children’s neurodevelopment of reading is affected by China’s language input system in the information era

Abstract: Communications through electronic devices require knowledge in typewriting, typically with the pinyin input method in China. Yet, the over utilization of the pronunciation-based pinyin input method may violate the traditional learning processes of written Chinese, which involves abundant visual orthographic analysis of characters and repeated writing. We used functional magnetic resonance imaging to examine the influence of pinyin typing on reading neurodevelopment of intermediate Chinese readers (age 9-11). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Four brief introductions of Hans Christian Andersen’s fairytale stories in a Chinese extracurricular book were edited as the materials for the reading task ( Zhou et al, 2020 ). Each story was presented in one block with 10 sentence trials.…”
Section: Methodsmentioning
confidence: 99%
“…Four brief introductions of Hans Christian Andersen’s fairytale stories in a Chinese extracurricular book were edited as the materials for the reading task ( Zhou et al, 2020 ). Each story was presented in one block with 10 sentence trials.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the pictographic origin and logographic nature of the Chinese script, Chinese characters consist of a three-tier structure: strokes are the small units that form a radical, and one or more radicals are grouped to construct a character. This complex, nonlinear configuration of characters require years of study in order to acquire adequate and accurate visuospatial processing in Chinese reading (Zhou et al, 2020). Importantly, previous research shows the write-to-read effect (Guan et al, 2011, Zhang & Reilly, 2015 and the importance of handwriting-to-character recognition (Cao et al, 2013;Mangen et al, 2015).…”
Section: Teaching Chinese Characters Online: the Status Quomentioning
confidence: 99%
“…However, online teaching means pedagogical practice has to rely on digital input rather than pen and paper, which minimises the opportunities for handwriting. One of the main input methods -indeed, the most popular in China -is pinyin input (Zhang & Min, 2019;Zhou et al, 2020). This requires knowledge of the sound of the Chinese characters, as pinyin is the system of romanising character pronunciation.…”
Section: Teaching Chinese Characters Online: the Status Quomentioning
confidence: 99%
See 1 more Smart Citation
“…A recent fMRI study by Zhou et al further demonstrated the impact of pinyin typing on neurodevelopment of reading in Chinese school-aged children (17). They found that more frequent usage of pinyin typing and digital devices in children was associated with overall weaker cortical activations, weaker functional connections, and reduced gray matter volume within the reading cortical network, suggesting that reliance on typewriting over handwriting may interfere with children's neurodevelopment of reading.…”
mentioning
confidence: 96%